Application of MURDER Learning Strategy to Improve Students' Understanding Ability on Islamic Education Lesson - Emi Lilawati; Dian Kusuma Wardani; Muhammad Khoirul Niam (SCHOOLAR: Social and Literature Study in Education, 2022)
This study uses quantitative methods. The purpose of this study is to uncover the phenomena that exist in schools at Sma Negeri Plandaan Jombang then this study is titled Application of Learning Strategy MURDER to Improve Students' Comprehension Skills in PAI Materials in Jombang State School. The population of this study is students of grade XI IPA 2 of Plandaan Jombang State High School. as a research class, as many as 35 students as experiman class use pots-test validation test method and pret-test that there are differences in pretest and posttest values in class XI IPA 2. Visually this shows that the use of MURDER strategy on PAI material in class XI IPA 2 is quite successful as seen from the higher posttest value of pretest. and student learning outcomes While the results of the analysis using paired t-tests get significant score results of 0.000 > 0.051 so it can be said that there is an influence on the use of Murder strategy in PAI Learning more effectively, on student learning outcomes.